The intensional profiles of five Hungarian imperative sentence types - Kleiber, Judit (Linguistica (Ljubljana), 2016)
The paper investigates Hungarian imperative sentence types from a pragmaticosemantic point of view. In addition to the baseline imperative, it analyzes types with non-standard intonation pattern and/or discourse markers. We apply the (S)DRT-based discourse-semantic framework of ReALIS for the examination and representation of five form-function pairs. The discussed types are all assigned an intensional profile which encodes the interlocutors' beliefs, desires and intentions (from the addresser's perspective). The analysis derives the different meanings of the variants from parametric differences.
Keywords: hongrois; Hungarian; madžarščina; phrase impérative; pragmatika; pragmatique; semantics; semantika; sémantique; skladnja; syntax; syntaxe; velelni stavek